Profile of higher order thinking ability in differentiation-based problem-based learning models - Satia Zulfiani Rosyid; Setiono Setiono; Billyardi Ramdhan (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
The high-level thinking abilities of students in Indonesia still need to improve. This is shown by the results of international studies such as PISA and TIMSS; Indonesia's ranking in these programs still needs to be at a higher level. Therefore, this research aims to determine the profile of high-level thinking abilities in problem-based learning differentiation. The method used is quantitative descriptive. The research subjects were MAN 2 Sukabumi City students, with a total of 26 students. The sampling technique, namely purposive sampling, is based on the student's ability to see a problem and play an active role in the learning process. This is based on recommendations from the subject teacher. This research shows that the N-gain value for high-level thinking abilities in the upper, middle, and lower groups is in the medium category, namely in the upper group with a value of 0.64, the middle group with 0.37, and the lower group with a value of 0.36. Therefore, differentiation-based problem-based learning (PBL) is effective for all groups in improving high-level thinking abilities.AbstrakKemampuan berpikir tingkat tinggi peserta didik di Indonesia masih cukup rendah hal ini ditunjukan dari hasil studi internasional seperti PISA dan TIMSS, peringkat Indonesia pada program tersebut masih berada ditingkat rendah oleh karena itu, penelitian ini bertujuan mengetahui profil kemampuan berpikir tingkat tinggi pada pembelajaran problem based learning berbasis diferensiasi, Metode yang digunakan yaitu deskriptif kuantitatif. Subjek penelitian adalah peserta didik MAN 2 Kota Sukabumi dengan jumlah 26 peserta didik. Teknik sampling yaitu purposive sampling berdasarkan dari kemampuan peserta didik dalam melihat suatu permasalahan dan berperan aktif dalam proses pembelajaran hal ini didasarkan atas rekomendasi dari guru mata pelajaran. Hasil penelitian ini menunjukan nilai N-gain pada kemampuan berpikir tingkat tinggi pada kelompok atas, tengah dan bawah ini berada pada kategori sedang yaitu pada kelompok atas dengan nilai 0,64, kelompok tengah 0,37 dan kelompok bawah mendapat nilai 0,36. Oleh karena itu pembelajaran problem based learning (PBL) berbasis diferensiasi ini efektif untuk semua kelompok dalam meningkatkan kemampuan berpikir tingkat tinggi.